Clinical profile of interstitial lung disease in children from Western India - Balaji, Mounnish; Chandane, Parmarth; Chauhan, Avantika; Rane, Atul; Bhosale, Alpa (International Journal of Contemporary Pediatrics, 2025)
Background: The epidemiology of interstitial lung disease in children (chILD) remains largely unknown, particularly in developing countries. This study aims to estimate the spectrum of ILD in children in India Methods: We retrospectively analysed data from consecutive subjects aged 0 to 18 years with interstitial lung diseases (ILD) recorded in the hospital registry at the Paediatric Respiratory Unit of Bai Jerbai Wadia Institute of Child Health from January 2018 to December 2023. We determined the proportion of each ILD subtype among children. Results: Out of 30 enrolled children, 60% were male. Symptoms began within the first year in 17 (56%) children, predominantly with a dry cough (77%) and dyspnea. Respiratory compromise signs were common, including tachypnea, tachycardia and hypoxemia, with 17% exhibiting clubbing. Chest X-rays showed reticular/reticulonodular patterns (63%) and HRCT revealed ground glass opacities (63%). Lung function tests indicated a restrictive pattern in 33%. Bronchoscopy aided in diagnosing pulmonary alveolar proteinosis, hypersensitive pneumonitis and diffuse alveolar hemorrhage. Genetic analysis (43% cases) identified surfactant protein disorder as the most common (13%). ILD subtypes included pulmonary hemosiderosis (23%), surfactant protein disorder, pulmonary alveolar proteinosis and Langerhans cell histiocytosis (each 13%). Conclusions: In Western India, Paediatric interstitial lung diseases exhibit a different pattern compared to adults. Pulmonary hemosiderosis spectrum, pulmonary alveolar proteinosis and surfactant protein disorder emerge as the predominant burdens among children.